Development of dynamic cell and organotypic skin models, for the investigation of a novel visco-elastic burns treatment using molecular and cellular approaches. Issue 7 (November 2020) - Wallace, Robert G.; Kenealy, Mary-Rose; Brady, Aidan J.; Twomey, Laura; Duffy, Emer; Degryse, Bernard; Caballero-Lima, David; Moyna, Niall M.; Custaud, Marc-Antoine; Meade-Murphy, Gerardene; Morrin, Aoife; Murphy, Ronan P.
Highlights: Novel versatile emergency burn dressing (EBD) saturated in a >90% translucent water-based, sterile, oil-free gel. New EBD impregnated with a proprietary biomarine complex (MXC). MXC is a natural bio-conditioning agent with benefits to burn healing and the prevention of scarring. Novel EBD + MXC hydrates, cools, relieves pain and provides a biocidal environment. EBD + MXC is ideal for use in pre-hospital, pre-surgical and resource limited settings. Abstract: Background: Burn injuries are a major cause of morbidity and mortality worldwide. Despite advances in therapeutic strategies for the management of patients with severe burns, the sequelae are pathophysiologically profound, up to the systemic and metabolic levels. Management of patients with a severe burn injury is a long-term, complex process, with treatment dependent on the degree and location of the burn and total body surface area (TBSA) affected. In adverse conditions with limited resources, efficient triage, stabilisation, and rapid transfer to a specialised intensive care burn centre is necessary to provide optimal outcomes. This initial lag time and the form of primary treatment initiated, from injury to specialist care, is crucial for the burn patient. This study aims to investigate the efficacy of a novel visco-elastic burn dressing with a proprietary bio-stimulatory marine mineral complex (MXC) as a primary care treatment to initiate a healthy healing process prior to specialist care. Methods: A new versatile emergency burn dressing saturated in a >90% translucent water-based, sterile, oil-free gel and carrying a unique bio-stimulatory marine mineral complex (MXC) was developed. This dressing was tested using LabSkin as a burn model platform. LabSkin a novel cellular 3D-dermal organotypic full thickness human skin equivalent, incorporating fully-differentiated dermal and epidermal components that functionally models skin. Cell and molecular analysis was carried out by in vitro Real-Time Cellular Analysis (RTCA), thermal analysis, and focused transcriptomic array profiling for quantitative gene expression analysis, interrogating both wound healing and fibrosis/scarring molecular pathways. In vivo analysis was also performed to assess the bio-mechanical and physiological effects of this novel dressing on human skin. Results: This hybrid emergency burn dressing (EBD) with MXC was hypoallergenic, and improved the barrier function of skin resulting in increased hydration up to 24 h. It was demonstrated to effectively initiate cooling upon application, limiting the continuous burn effect and preventing local tissue from damage and necrosis. xCELLigence RTCA® on primary human dermal cells (keratinocyte, fibroblast and micro-vascular endothelial) demonstrated improved cellular function with respect to tensegrity, migration, proliferation and cell-cell contact (barrier formation) [1 ]. Quantitative gene profiling supported the physiological and cellular function finding. A beneficial quid pro quo regulation of genes involved in wound healing and fibrosis formation was observed at 24 and 48 h time points. Conclusion: Utilisation of this EBD + MXC as a primary treatment is an effective and easily applicable treatment in cases of burn injury, proving both a cooling and hydrating environment for the wound. It regulates inflammation and promotes healing in preparation for specialised secondary burn wound management. Moreover, it promotes a healthy remodelling phenotype that may potentially mitigate scarring. Based on our findings, this EBD + MXC is ideal for use in all pre-hospital, pre-surgical and resource limited settings.